Psycholegal Analysis of Nurses’ Decision-Making in Patient Treatment Refusal: A Human Rights Perspective in Indonesia - Aris Prio Agus Santoso; Domingos Soares; Ady Irawan AM (Universitas Lampung, 2025)
The ethical challenges nurses face when patients refuse treatment—a legally protected right often complicated by normative, ethical, and social factors. It investigates how nurses reconcile respect for patient autonomy with their psycholegal responsibilities under Indonesian law. Using a normative juridical approach and thematic analysis of relevant documents, the research uniquely applies human rights theory to nursing decision-making in treatment refusal cases an underexplored perspective in Indonesian health law. Findings confirm that Article 276 of Law No. 17 of 2023, alongside international human rights frameworks and Islamic law, safeguards patients’ right to refuse treatment. When refusal is informed and voluntary, healthcare providers are legally protected. The research concludes that nurses must support patient autonomy through therapeutic communication, psycholegal awareness, and meticulous documentation.